An adaptive warning message scheme for emergency vehicles using vehicular ad hoc communication - Banikhalaf, Mustafa; Hammad, Rafat; Al-Dubai, Ahmed; Ghaleb, Baraq (International Journal of Engineering and Technology, 2026)
Nowadays, traffic management has been a challenging task due to the growing number of vehicles. More specifically, operation management of Emergency Vehicles (EVs) such as ambulances, police force and fire fighting vehicles require extensive industrial and academic studies. The research community has been placing a great deal of emphasis for reducing the travelling time of the EV between the starting point and the destination point. In the foreseeable future, all vehicles are assumed to be fully equipped with wireless technology. This facilitates communication and coordination between vehicles and traffic lights, and shortens the time needed for EVs to reach their destinations. This paper focuses on developing an efficient broadcast algorithm, namely, Adaptive Warning Message Scheme (AWMS), using Vehicle-to-Vehicle (V2V) communication, to deliver a Warning Message (WM) as quickly as possible to a target traffic light. In the AWMS, a high priority message dissemination is given to WMs, which are responsible for informing the traffic light about any approaching EVs, while a low dissemination priority is assigned to normal Information Messages (IMs), (i.e. messages that carry general information about a vehicle). In addition, the EV direction toward a traffic light is considered in our scheme when broadcasting the WM to reduce the broadcast storm problem. Time delay between two consecutive WMs is calculated based on the EV speed and traffic density. The simulation results have shown that the AWMS has the capacity and ability to disseminate WMs with minimum number of retransmissions, collision rate and end-to-end delay.